Determinants and Functions of CAFs Secretome During Cancer Progression and Therapy - Linares, Jenniffer; Marín-Jiménez, Juan A.; Badia-Ramentol, Jordi; Calon, Alexandre (Frontiers in Cell and Developmental Biology, 2021)
Multiple lines of evidence are indicating that cancer development and malignant progression are not only epithelial cancer cell-autonomous processes but may also depend on crosstalk with the surrounding tumor microenvironment (TME). Cancer-associated fibroblasts (CAFs) are abundantly represented in the TME and are continuously interacting with cancer cells. CAFs are regulating key mechanisms during progression to metastasis and response to treatment by enhancing notably cancer cells survival and aggressiveness. Recent advances in CAFs biology have underscored the potential of CAFs-secreted factors as actionable biomarkers for cancer diagnosis, prognosis and treatment. In this review, we explore current understanding of CAFs secretome determinants and functions to discuss their clinical implications in oncology.